Radikalisasi Makna Jihad di Era Modern: Studi Kasus Penafsiran QS. Al-Taubah: 73 Menurut Sayyid Qutb dan Abu A’la al-Maududi - Nur Fadli Yati; Kusmana Kusmana (JOURNAL OF QUR'AN AND HADITH STUDIES, 2021)
This paper discusses the meaning of jihad in QS. At-Taubah: 73 according to two modern interpreters: Sayyid Qutub and Abul A'la Mawdudi. Their interpretation is very important because their thinking is an important reference in the current discourse of Jihad. With the descriptive-analytic method, the writing answers how the two Muslim thinkers interpreted the term jihad in the verse which supports the spirit of their respective da'wah movements in Egypt and Pakistan. This paper finds that the second author in interpreting the term jihad by the objective circumstances of their respective life contexts, Sayyid Qutb was influenced by the fact that some Muslims dealt with rulers who were considered dholim, and Egypt as a country is in a war conflict with Israel, as well as the resistance of some Muslim scholars including himself who are critical of the West. Meanwhile, Abul A'la Mawdudi was faced with the filling of the newly established Pakistani state, where he and his colleagues was founded political parties that were in the spirit of Islam. More than that, his romanticist attitude towards the early period of the Muslim community was used as a manhaj in understanding the messages of the Qur'an.